Russia and Nato: between competition and cooperation. From the end of the Cold war to the Pratica di mare agreement (1991-2002) - Bianchi, Giulia (Studi Politici, 2022)
In the light of newly arisen tensions between NATO and Russia, this article attempts to look at the development of NATO-Russia relations in a broad historical perspective. Drawing on declassified diplomatic documentation from Soviet/Russian and US archives as well as on most recent literature, it deals in particular with Russia’s vision and pursuit of a revisited European security system in the years following the end of the Cold War. In doing so, it also examines the different strategies followed by Russia’s leadership with respect to the problem of NATO’s transformation and enlargement after the Cold War.